The Clinical Accuracy of the BÜHLMANN fCAL ELISA in the Differentiation of Inflammatory Bowel Disease From Irritable Bowel Syndrome: A Multicenter Prospective Case–Control Study. Issue 3 (5th October 2019) - Berinstein, Jeffrey A; Steiner, Calen A; Bousvaros, Athos; Tiongco, Felix P; Greenberg, Eugene; Hardi, Robert; Lembo, Anthony J; Friedenberg, Keith; Sedghi, Shahriar; Fint, Alison; Florez, David A; Kumar, Ashutosh; et al.
Abstract: Background: Fecal calprotectin (fCAL) is a noninvasive biomarker used to differentiate between inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS). Methods: A multicenter prospective case–control study evaluating the BÜHLMANN fCAL enzyme-linked immunosorbent assay (ELISA) was conducted in 478 subjects. Sensitivity, specificity, predictive values, and area under the receiver operator characteristic (AuROC) curve are reported and compared to another device. Results: In differentiating IBD from IBS, the BÜHLMANN fCAL ELISA is very sensitive (93.3%) at a cutoff <80 μg/g and balanced sensitivity (84.4%) and specificity (85.4%) at a cutoff >160 μg/g (AuROC 0.933). Conclusions: The BÜHLMANN fCAL ELISA demonstrates excellent discriminating between IBD and IBS. Lay Summary: In a large, multicenter, case–control study, we demonstrate that the BÜHLMANN fecal calprotectin enzyme-linked immunosorbent assay can reliably predict inflammation with sufficiently high specificity in both adult and pediatric inflammatory bowel disease compared to irritable bowel syndrome.